A Comparison of Parenteral Phenobarbital vs. Parenteral Phenytoin as Second-Line Management for Pediatric Convulsive Status Epilepticus in a Resource-Limited Setting - Burman, Richard J.; Ackermann, Sally; Shapson-Coe, Alexander; Ndondo, Alvin; Buys, Heloise; Wilmshurst, Jo M. (Frontiers in Neurology, 2019)
Paediatric convulsive status epilepticus (CSE) which is refractory to first-line benzodiazepines is a significant clinical challenge, especially within resource-limited countries. Parenteral phenobarbital is widely used in Africa as second-line agent for paediatric CSE, however evidence to support its use is limited. This study aimed to compare the use of parenteral phenobarbital against parenteral phenytoin as a second-line agent in the management of paediatric CSE. An open-labelled single-centre randomized parallel clinical trial was undertaken which included all children (between ages of one month to 15 years) who presented with CSE. Children were allocated to receive either parenteral phenobarbital or parenteral phenytoin if they did not respond to first-line benzodiazepines. An intention-to-treat analysis was performed with the investigators blinded to the treatment arms. The primary outcome measure was the success of terminating CSE. Secondary outcomes included the need for admission to the paediatric intensive care unit (PICU) and breakthrough seizures during the admission. In addition, local epidemiological data was collected on the burden of paediatric CSE. Between 2015 – 2018, 193 episodes of CSE from 111 children were enrolled in the study of which 144 met the study requirements. Fourty-two percent had a prior history of epilepsy mostly from structural brain pathology (53%). The most common presentation was generalized CSE (65%) caused by acute injuries or infections of the central nervous system (49%), with 19% of children having febrile status epilepticus. Thirty-five percent of children required second-line management. More patients who received parenteral phenobarbital were at a significantly reduced risk of failing second-line treatment compared to those who received parenteral phenytoin (RR = 0.3, p = 0.0003). Phenobarbital also terminated refractory CSE faster (p <0.0001). Furthermore, patients who received parenteral phenobarbital were less likely to need admission to the PICU. There was no difference between the two groups in the number of breakthrough seizures that occurred during admission. Overall this study supports anecdotal evidence that phenobarbital is a safe and effective second-line treatment for the management of paediatric CSE. These results advocate for parenteral phenobarbital to remain available to health care providers managing paediatric CSE in resource-limited settings.